53.4k views
0 votes
Solve the equation.

y + 6 = –3y + 26

y = –8
y = –5
y = 5
y = 8

User Jpshook
by
6.2k points

2 Answers

6 votes

Answer:

Explanation:

5

User Cerulean
by
5.3k points
4 votes

For this case we have the following equation:


y + 6 = -3y + 26

To clear the value of and we have the following steps:

1st step:

We subtract 6 on both sides of the equation:


y + 6-6 = -3y + 26-6\\y = -3y + 20

2nd step:

We subtract "y" from both sides of the equation:


y-y = -3y-y + 20\\0 = -4y + 20

3rd step:

We add
4y to both sides of the equation:


0 + 4y = -4y + 4y + 20\\4y = 20

4th step:

We divide between 4 sides of the equation:


(4y)/(4)=(20)/(4)\\y = 5

Thus, the value of y is 5.

Answer:


y = 5

Option C


User Adam Hopkins
by
4.7k points